Michaelangelo artist and man - Friedman, Adam; Friedman, Adam; Markham, Monte; Markham, Monte (New Video Group, 1994)
He is one of the greatest artist of all time, a man whose name has become synonymous with the word "masterpiece": Michaelangelo Buonarotti.